Collocational error types in the writing of Iranian EFL students / Marjan Ahmadi - Ahmadi, Marjan (2012)
Collocations are one of the most important concerns in EFL classes and materials. The significance of second language learners possessing some knowledge of collocaitons is now widely recognized. The learning of collocations can provide advantages such as increasing learners‟ language competence and also enhancing learners‟ communicative competence. Hence collocation knowledge is essential for EFL learners while collocation instructions in EFL courses become a necessity. EFL learners such as Persian learners of English make many collocational errors in their writing and in their speaking due to a lack of collocation competence in English. For instance, Persian/Iranian EFL learners say “learn knowledge” rather than “gain/acquire knowledge”, because in Persian the noun “knowledge” co-occurs with the verb “learn” instead of “gain/acquire”. Due to this gap, it would seem necessary for teachers teaching EFL in Iran to enhance their own collocation knowledge and through this competence; they can help to raise the awareness of EFL learners‟ errors. Hence, it would pay for the education ministry, curriculum designers and teachers to help EFL learners to pay attention to their mis-collocations when producing the target language. In this way, EFL learners find out that it is necessary for them not only to learn new words but also to be familiar with word combinations. The purpose of the present study is to investigate what kind of collocation errors are made by Iranian EFL university learners and also to attempt to identify the collocational error types and the frequency of collocation error types made by Iranian postgraduates in their writing. In addition, the sources of Iranian EFL university learners‟ collocation errors are also discussed in the present study. present study, the definition of collocations focused on co-occurrence of words. The subjects in the present study are 60 Iranian postgraduate university students studying at a public university in Malaysia. They had all studied English as a foreign language in guidance school and high school for 6 years, graduated from high schools. All of them have passed the Academic Writing course offered by the university they are attending and an English course which is a mandatory course for the completion of their degree. They have been here at least for 2 years. The subjects‟ ages are between 22 and 35 and all of them are native speakers of Persian. The data were collected from the subjects. The data included 60 copies of the subjects‟ writing samples. The subjects were asked to write on one of three topics provided to them as tasks and the length can be around 150-200 words. The unacceptable grammatical and lexical collocational errors were then manually identified based on the classification of collocations proposed by Benson et al. (1986). The BBI Dictionary of English Word Combinations, Associated Concordancer, and TANGO (a national e-learning project established by National Science Council) were also employed to analyze the subjects‟ collocational error and to provide suggestions for correction. After analyzing the collected data, a total of 1664 collocations were found in the subjects‟ writings. Out of the 1664 collocations, 602 were lexical collocations and 1062 were grammatical collocations. From these total, it seems that the subjects had made 354 lexical collocational errors and only 71 grammatical collocational errors. So, the results showed that there were more lexical collocational errors (60.12 %) than grammatical collocational errors (7.42%) and this conforms to the hypothesis of the present study that